The Effectiveness of Look-Say Method on Teaching Reading Comprhension on The Eighth Grade Students at SMPN 1 Konawe - Hasmirawati Injar Lasitiha (Journal of International Multidisciplinary Research, 2024)
This research aims to determine how the effect of using the look and say method on learning acheivemnt reading comprehension for class VIII D students of SMPN 1 Konawe. The researcher problems were “Is there any significanct effect on students’ English reading comprehension before and after taught by using look and say strategy? And Is there any significant difference on students’ English reading comprehension taught by using look and say strategy and those are not?”. This research uses a type of pre-experimental design research with One Group Pretest-Posttest Design. The subjects of this study were students of class VIII D SMPN 1 Konawe totally was 22 students. Data collection techniques were carried out using tests those are pretest, treatment, and posttest. The data collected were analyzed quantitatively using descriptive statistics and inferential statistics. The researcher used theory of Edhitin (2000) to analyzed the data. The results of quantitative analysis show that the results of descriptive statistical data shows that there are differences in the learning acheivement of students' reading comprehension which are marked by the mean score of students who are in the implementation the pretest was 56,59 while in the posttest the students' average score was 70,91. The results of inferential statistical data show that t test > t table or 6,539 > t table = 2,086 if viewed from the results of the pretest and posttest hypothesis tests it is known that t test > t table or 7,936 > 2.086, it can be concluded that H0 is rejected and Ha is accepted. This means that there is an influence of look and say methode on the reading comprehension learning achievement of class VIII D students of SMPN 1 Konawe.